Experimental and theoretical study of charge transfer in hydrogen ion scattering from a graphite surface - Bonetto, Fernando Jose (2007)
Ion scattering spectrometry (ISS) with time of flight (TOF) analysis is employed to measure the ion fraction of positively charged hydrogen (H+) projectiles scattered from a well characterized highly oriented pyrolitc graphite (HOPG) surface at a 458 scattering angle, various ingoing/outgoing angles and two different incoming energies (4 and 5 keV). In the theoretical approach, the negative ionization probability is calculated by employing a Green’s function formalism to solve the dynamic collisional process. Both theoretical and experimental results are analyzed and contrasted. The theoretical negative ion fraction evolution during the collisional process is described in detail.